PERENCANAAN PENGADAAN OBAT DI RUMAH SAKIT UMUM DAERAH (RSUD) KABUPATEN KEPULAUAN MERANTI - ", Romauli; Sahuri, Chalid (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2016)
Medicine procurement planning is an activity that is conducted in order to compile a list of Medicine -related needs of a guideline on the basis of the concept of systematic activities with a logical sequence in achieving the goals or objectives that have been set. Medicine procurement planning carried out by the regional general hospital have not been part of the Island District felt the maximum because there is still a case of the vacuum medicine. The purpose of this research is to find out and analyze how the implementation planning for the procurement of Medicines in general hospitas. District Areas of the Islands and to find out the factors that influence the implementation of Medicine procurement planning in the area of public hospitals Island Regency.The concept of the theory is a theory that the author use Moch Imron, there are 3 (Three) planning indicators, namely : policy, procedure and budget. This research uses qualitative research methods with the study of descriptive data. In data collection, the author uses interview techniques, observation and documentation. With the use of key informants as a source of information and technique of triangulation as a source in the validity of the data.The results of this study showed that the Medicine procurement planning in the area of public hospital have not been part of the Island District is running optimally, attested from the occurrence of the vacancy still a Medicine that took place from 2013, remains the lack of medical personnel, which resulted in patterns of prescribing change – change thereby affecting Medicine consumption patterns with planning that have been made, and the lack of a budget that affect the amount of the Medicine that will be conducted by the Meranti’s hospital is part of Island District. The factors that inhibit the Medicine procurement planning in the area of public hospital Island Regency is still the lack of medical personnel, facilities and infrastructure as well as material Medicines that do not exist in the distributor so that the Medicine can't be held.Key Words: Planning, Procurement, Medicine